Advances in cell-based delivery of oncolytic viruses as therapy for lung cancer - Giti Esmail Nia; Elahe Nikpayam; Molood Farrokhi; Azam Bolhassani; Ralph Meuwissen (Molecular Therapy: Oncology)
Lung cancer’s intractability is enhanced by its frequent resistance to (chemo)therapy and often high relapse rates that make it the leading cause of cancer death worldwide. Improvement of therapy efficacy is a crucial issue that might lead to a significant advance in the treatment of lung cancer. Oncolytic viruses are desirable combination partners in the developing field of cancer immunotherapy due to their direct cytotoxic effects and ability to elicit an immune response. Systemic oncolytic virus administration through intravenous injection should ideally lead to the highest efficacy in oncolytic activity. However, this is often hampered by the prevalence of host-specific, anti-viral immune responses. One way to achieve more efficient systemic oncolytic virus delivery is through better protection against neutralization by several components of the host immune system. Carrier cells, which can even have innate tumor tropism, have shown their appropriateness as effective vehicles for systemic oncolytic virus infection through circumventing restrictive features of the immune system and can warrant oncolytic virus delivery to tumors. In this overview, we summarize promising results from studies in which carrier cells have shown their usefulness for improved systemic oncolytic virus delivery and better oncolytic virus therapy against lung cancer.